Use of generalized Procrustes analysis (GPA) to test the effects of sex and carcass weight on sensory quality evaluations of Terrincho lamb meat - Rodrigues, Sandra (2013)
Generalized Procrustes analysis (GPA) was used to test the sensory attributes of Terrincho lamb meat, a product with Protected Designation of Origin (PDO) labelling. Effects of sex and carcass weight on the following sensory attributes: toughness, juiciness, flavour intensity, odour intensity, stringiness, and level of sweetness were tested. Tests were performed on 28 females and 29 males placed within three classes of carcass weight, 3 to 9 kg. Meat sensory quality was evaluated, within five sessions, by a trained taste panel. Meat was cooked in a conventional oven, cut into pieces, and delivered to the panel for evaluation. Data were analyzed using a GPA to minimize differences between assessors. Two factors explained 72.76% of the total variability. The panel did not clearly detect sex effects, yet could differentiate meat by carcass weight as heavier animals were toughest and had more intense odour and flavour, whilst light animals were most succulent.